Analisis Penggunaan Digital Payment bagi Pelaku UMKM di Kawasan Objek Wisata Belanja Citra Niaga Kota Samarinda - Salsabila, Salsabila -; Abu, Ilham; Reza, Reza (Jurnal Ilmiah Wahana Pendidikan, 2024)
Citra Niaga is a trading area that sells handicrafts typical of Samarinda culture and is the central business area for the city of Samarinda. The existence of technological advances in the business world can be utilized by MSME actors in various fields, one of which is the payment system. Digital Payment is a payment process that is done using technology. Currently, people prefer to use online payments, but there are still business actors in citra niaga who have not implemented a digital payment system in their business. The purpose of this study is to identify the causes and impact of the factors of the use of digital payment. This study uses a descriptive type of research with a qualitative approach. Data collection was conducted by interviews with business actors souvenirs or souvenirs typical of East Kalimantan in the area of shopping attractions Citra Niaga Samarinda. There are three data analysis used in this study, namely data reduction, data presentation, and conclusion. The results of the interviews showed that the use of digital payments is very beneficial, considered effective and efficient by informants. They highlight the ease, acceleration, and convenience in digital transactions. Therefore, the use of digital payments significantly increases the effectiveness, efficiency and convenience in the transaction process, as well as providing convenience for all parties involved. Based on the results of the above research, that the business of souvenirs and souvenirs typical of East Kalimantan in the area of shopping attractions Citra Niaga Samarinda has used digital payment in payment transactions. Although digital payments provide great benefits, users also feel anxious because of the risk of fraud. Therefore, service providers need to continuously improve the security and quality of their services to reduce these risks and build user trust.